Mapeamento dos níveis de poluição atmosférica em torno de escolas públicas da cidade de Porto Alegre - Eidt, Carina Saraiva (2013)
Objective : To describe the levels of pollution in of public schools from the city of Porto Alegre, as well as to estimate the behavior of the different methodologies used to evaluate the concentration of pollutants. Methods : We measured the levels of pollutants that students are exposed in public schools from Porto Alegre. The distance from schools and homes to the avenue of higher vehicle traffic was estimated, and the levels of particulate matter of 2.5μm (MP2.5) in the microenvironments of the schools were measured, both at selected and moving points. Conclusion : This study indicates that a significant number of schools in the city of Porto Alegre and students residencies are located in places with air pollution levels considered risky to health according to the World Health Organization and the level of agreement between the methods used for pollution evaluation, were lower than expected. Results : Nine public schools of Porto Alegre were included and a total of 196 students. Thirty three percent of schools were within 400 meters of distance to a big avenue, a distance considered risky; the number of students living within 400 meters to a big avenue was 96 (49%). Eighty two students (42%) were exposed to MP2.5 levels above 25 mcg / m³, considered risky to health, during their pathway from home to school; at the indoor environment, 29 students (15%) and 53 students to outdoor environment (27%). The agreement between the methods used at the most polluted places Kappa values ranged from -0.443 (measured indoor) to 0.422 (measured outdoor).Conclusion : This study indicates that a significant number of schools in the city of Porto Alegre and students residencies are located in places with air pollution levels considered risky to health according to the World Health Organization and the level of agreement between the methods used for pollution evaluation, were lower than expected.